A method for determining in 3-D, the true dip and azimuth of a reflecting horizon - Evans, Brian; Uren, N.; McDonald, J. (2018)
A 3-D field method has been devised in which the true dip of a reflecting horizon and its azimuth can be measured within a survey area. The method requires a suitable horizon to which the velocity is known, and assumes that the reflecting horizon has constant dip throughout the area. Two orthogonal swath surveys are performed, and data are stacked using variable dip and strike values. A 3-D NM0 equation corrects data to a zero-offset reference point. An optimum value of dip and strike provides the best reflection line-up at the reference point, producing the value of true dip and its azimuth for that horizon. A physical model was used to demonstrate the method, which was able to predict dips and their azimuths to within half a degree.